Hubungan Pengetahuan tentang Hipertensi dengan Pengendalian Tekanan Darah pada Pasien Hipertensi Dewasa - Misyel Patandianan; Chrispian Oktafbipian Mamudi; Suzanna Ndraha (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Hypertension is the main culprit of cardiovascular disease globally, and the leading cause of early death in the whole world. Success of hypertension therapy and blood pressure control is attributed to multiple factors, such as medication adherence. Medication adherence itself is also found to be attributed to multiple factors, one of them is knowledge. Several studies analyzed in this research stated similar results, that knowledge of hypertension is one of the detemining factors in blood pressure control on hypertensive adult patients. The components of such knowledge that needs to be paid attention to is medication adherence, healthy lifestyle, salt intake, and knowing blood pressure control target.